Is educational attainment associated with acute exposure to air pollution and pollen, and is it worse for pupils with asthma and seasonal allergic rhinitis?. (2018) - Mizen, Amy; Lyons, Jane; Akbari, Ashley; Berridge, Damon; Carruthers, David; Davies, Gwyneth; Dearden, Lorraine; Doherty, Ruth; Mavrogianni, Anna; Lake, Iain; Rodgers, Sarah
No abstract available